S in Geoinformatics Profession - Sharma, Rabin K. (Journal on Geoinformatics, Nepal, 2017)
The researchers from the field of surveying, in which the first letter of the word surveying is "S", is always seeking to improve for efficient system. In the process of such development, geoinformatics word being used instead of surveying and it covers wide range of technologies to collect, process, visualize, storage, integrate and disseminate the data and information required for many applications to improve the livelihood of the people. This article tried to identify such system related to the alphabet "S". Nepalese Journal on Geoinformatics, Vol. 14, 2015, Page: 37-40